Traditional and nontraditional glycemic markers and risk of peripheral artery disease: The Atherosclerosis Risk in Communities (ARIC) study. (July 2018) - Ding, Ning; Kwak, Lucia; Ballew, Shoshana H.; Jaar, Bernard; Hoogeveen, Ron C.; Ballantyne, Christie M.; Sharrett, A. Richey; Folsom, Aaron R.; Heiss, Gerardo; Salameh, Maya; Coresh, Josef; Hirsch, Alan T.; et al.
Abstract: Background and aims: Traditional glycemic markers, fasting glucose and hemoglobin A1c (HbA1c), predict incident peripheral artery disease (PAD). However, it is unknown whether nontraditional glycemic markers, fructosamine, glycated albumin, and 1, 5-anhydroglucitol, are associated with PAD and whether these glycemic markers demonstrate particularly strong associations with severe PAD, critical limb ischemia (CLI). Methods: We quantified the associations of these five glycemic markers with incident PAD (hospitalizations with PAD diagnosis or leg revascularization) in 11, 634 ARIC participants using Cox regression models. Participants were categorized according to diabetes diagnosis and clinical cut-points of glycemic markers (nontraditional glycemic markers were categorized according to percentiles corresponding to the HbA1c cut-points). Results: Over a median follow-up of 20.7 years, there were 392 cases of PAD (133 were CLI with tissue loss). HbA1c was more strongly associated with incident PAD than fasting glucose, with adjusted hazard ratios (HR) 6.00 (95% CI, 3.73–9.66) for diagnosed diabetes with HbA1c ≥ 7% and 3.53 (2.39–5.22) for no diagnosed diabetes with HbA1c ≥ 6.5% compared to no diagnosed diabetes with HbA1c <5.7%. Three nontraditional glycemic markers demonstrated risk gradients intermediate between HbA1c and fasting glucose and their risk gradients were substantially attenuated after adjusting for HbA1c. All glycemic markers consistently demonstrated stronger associations with CLI than PAD without CLI ( p for difference <0.02 for all glycemic markers). Conclusions: Nontraditional glycemic markers were associated with incident PAD independent of fasting glucose but not necessarily HbA1c. Our results also support the importance of glucose metabolism in the progression to CLI. Highlights: Nontraditional glycemic markers were significantly associated with incident PAD. All glycemic markers demonstrated particularly strong associations with CLI. HbA1c might be useful to identify patients who would benefit from foot care.